2021
DOI: 10.1111/trf.16524
|View full text |Cite
|
Sign up to set email alerts
|

Blood group O convalescent plasma donations have significantly lower levels of SARS‐CoV‐2 IgG antibodies compared to blood group A donations

Abstract: Background COVID‐19 convalescent plasma (CCP) is plasma collected from individuals who have recovered from SARS‐CoV‐2 infection. The FDA Emergency Use Authorization restricts use of CCP to high‐titer units only. The purpose of this study was to determine if donor ABO blood group was associated with SARS‐CoV‐2 antibody response, and subsequent qualification as high‐titer CCP. Methods All CCP donations collected from April 21, 2020 to September 1, 2020 were included. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
11
2
Order By: Relevance
“…Our results do not confirm the previous reports that the ABO blood group type affects the anti‐SARS‐CoV‐2 antibody concentration in COVID‐19 convalescents 19–22 . In our cohort, we found no statistically significant differences between the SARS‐CoV‐2 antibody levels in different ABO‐types regardless of which serological method was used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results do not confirm the previous reports that the ABO blood group type affects the anti‐SARS‐CoV‐2 antibody concentration in COVID‐19 convalescents 19–22 . In our cohort, we found no statistically significant differences between the SARS‐CoV‐2 antibody levels in different ABO‐types regardless of which serological method was used.…”
Section: Discussioncontrasting
confidence: 99%
“…[5][6][7][8][9][10] Therefore, it was logical that the following research would focus on the impact of ABO blood group type on the quantity of anti-SARS-CoV-2 antibodies produced in convalescents since the CCP represents a valuable resource for prevention and therapy. Since the resulting studies led to conflicting results, [16][17][18][19][20][21][22] we analyzed a larger cohort of 3187 COVID-19 convalescent plasma donors.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% of the Japanese population is estimated to have blood type AB [17], and a similar percentage of this blood type was observed in the present study. In accordance with our findings, previous studies have also reported that donors with blood type AB have higher antibody titers than those with blood type O [18,19] and that patients with COVID-19 have lower levels of ABO antibodies than uninfected individuals [20]. These findings indicate that blood type ABO may have some influence on the development of SARS-CoV-2 infection and antibody production.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Hayes et al showed that blood Type O had significantly lower levels of anti-N IgG compared to blood type A [ 50 ]. The other two studies reported lower levels of nAbs, anti-S and anti-RBD Abs in persons with blood type O compared to subjects with blood Types AB and B [ 18 , 51 ].…”
Section: Discussionmentioning
confidence: 99%